Macrogenomes reveal microbial-mediated microplastic degradation pathways in the porcine gut: a hope for solving the environmental challenges of microplastics - Wang, Tao; Luo, Yuheng; Yu, Bing; Zheng, Ping; Huang, Zhiqing; Mao, Xiangbing; Yu, Jie; Luo, Junqiu; Yan, Hui; He, Jun (Frontiers in Microbiology, 2024)
It is increasingly recognised that microplastics are being transmitted through the food chain system, but little is known about the microorganisms involved in microplastic degradation, functional biodegradation genes, and metabolic pathways of degradation in the intestinal tract of foodborne animals.In this study, we explored the potential flora mainly involved in microplastic degradation in the intestinal tracts of Taoyuan, Duroc, and Xiangcun pigs by macrogenomics, screened relevant microplastic degradation genes, and identified key enzymes and their mechanisms. The pig colon was enriched with abundant MP degradation-related genes, and gut microorganisms were their main hosts. The fiber diet did not significantly affect the abundance of MP degradation-related genes, but significantly reduced their diversity. We identified a total of 94 functional genes for microplastic degradation and classified them into 27 categories by substrate type, with PS (Polystyrene), PET (Polyethylene terephthalate), and DEHP (Di(2-ethylhexyl) phthalate) being the most predominant degradation types. The microplastic degradation functional genes were widely distributed in a variety of bacteria, mainly in the phylum Firmicutes and Bacteroidetes. Based on the identified functional genes for microplastic degradation, we proposed a hypothetical degradation mechanism for the three major microplastic pollutants, PS, PET, and DEHP, which mainly consists of oxidoreductase, hydrolase, transferase, ligase, laccase, and isomerase. The degradation process involves the breakdown of long polymer chains, oxidation of short-chain oligomers, conversion of catechols, and achievement of complete mineralization. Our findings provide insights into the function of MPs degradation genes and their host microorganisms in the porcine colon.